Identification and Optimization of the First Highly Selective GLUT1 Inhibitor BAY‐876. (23rd August 2016) - Siebeneicher, Holger; Cleve, Arwed; Rehwinkel, Hartmut; Neuhaus, Roland; Heisler, Iring; Müller, Thomas; Bauser, Marcus; Buchmann, Bernd
Abstract: Despite the long‐known fact that the facilitative glucose transporter GLUT1 is one of the key players safeguarding the increase in glucose consumption of many tumor entities even under conditions of normal oxygen supply (known as the Warburg effect), only few endeavors have been undertaken to find a GLUT1‐selective small‐molecule inhibitor. Because other transporters of the GLUT1 family are involved in crucial processes, these transporters should not be addressed by such an inhibitor. A high‐throughput screen against a library of ∼3 million compounds was performed to find a small molecule with this challenging potency and selectivity profile. The N ‐(1 H ‐pyrazol‐4‐yl)quinoline‐4‐carboxamides were identified as an excellent starting point for further compound optimization. After extensive structure–activity relationship explorations, single‐digit nanomolar inhibitors with a selectivity factor of >100 against GLUT2, GLUT3, and GLUT4 were obtained. The most promising compound, BAY‐876 [ N 4 ‐[1‐(4‐cyanobenzyl)‐5‐methyl‐3‐(trifluoromethyl)‐1 H ‐pyrazol‐4‐yl]‐7‐fluoroquinoline‐2, 4‐dicarboxamide], showed good metabolic stability in vitro and high oral bioavailability in vivo. Abstract : A GLUT of selectivity ! Based on an HTS hit, extensive SAR studies at all regions of the structure finally led to the very potent GLUT1 inhibitor BAY‐876, having more than 100‐fold selectivity against other GLUT members. The good in vitro and in vivo pharmacokinetics properties of BAY‐876 make it an excellent chemical probe to further evaluate the scope and limitations of GLUT1 inhibition as a new therapeutic option.